Nuclear corporate social responsibility: an approach toward a roadmap for gaining social confidence. (25th July 2007) - Sawada, T.; Tanaka, H.; Morimoto, T.; Oba, K.; Kuwabara, A.; Mizuo, J.
The term 'corporate social responsibility' (CSR) has been widely applied in the field of business administration. The essence of CSR is the idea, guidelines and methodology with regard to how a corporation can fulfil its responsibility to society. Recently, the concept and methodology of CSR, occasionally referred to as just SR, have also been applied to other organisations, such as research establishments and universities. A typical aspect of this trend is that most electric power companies publish CSR reports, which are an improved version of social-environmental reports. CSR embodies the expectations of society with respect to how far the corporations and organisations, including universities, can resolve the issues in which society is necessarily involved or that can bring about advancements in society. Nuclear power generation and related facilities are types of 'societal systems', and not merely technological systems. Society commits its necessary functions to the societal systems.